Ethnicity and patient satisfaction with tuberculosis care: A cross‐sectional study. (18th March 2015) - Mukasa, Jean P.; Glass, Nel; Mnatzaganian, George
Abstract Patients presenting in major tuberculosis (TB) centres in two Australian metropolitan hospitals and three central hospitals in Malawi were interviewed for health and other information, including their satisfaction with nursing care. The main objective of the study was to investigate differences in satisfaction rates among ethnically similar and different patients coming from two dissimilar health systems. A multivariable Generalized Estimating Equations model was constructed to identify sociodemographic and health‐related factors associated with dissatisfaction, while focusing on ethnic differences between and within each country. The Australian and Malawian patients were similar in age, gender, marital status, and employment. However, the Malawians were mostly inpatients, with recurrent TB episodes, and were more seriously ill with impaired physical and mental wellbeing. Nonetheless, being Australian was more associated with dissatisfaction observed in all components of care. However, Australian ethnic minorities were less dissatisfied than their Anglo‐Saxon or European counterparts, being more similar to Malawian patients irrespective of the health care provided. Our study suggests that patients coming from similar ethnic backgrounds may express similar satisfaction irrespective of the health system they belong to.